Tenkning i sykepleie om eksklusjon av foreldre ved barns innleggelse i sykehus - Hildegunn Sundal; Karin Anna Petersen; Jeanne Boge (Septentrio Academic Publishing, 2015)
Analyses of textbooks in nursing, of photographs and numerous other documents suggest that parents had limited access to participate in the care for their hospitalized children in Norway in the period 1877-1940. The analyses are conducted in the tradition of the French philosopher Michel Foucault's writings on discipline. In accordance with Foucault's understanding, it seems logical that ideas about parenting exclusion had impact even within the hospital health care system in the current era, provided the general separation of parents and children in the modern industrial society at large. In this perspective, exclusion of parents in the hospital health care system may be considered a consequence of employers' interests with regard to productivity, the lack of welfare services for parents, and the fear of parents transmitting infections from the hospitals.